Genetic characterization of the first detected human case of avian influenza A (H5N6) in Anhui Province, East China. Issue 1 (December 2018) - He, Jun; Liu, Bo-Yu; Gong, Lei; Chen, Zhen; Chen, Xiao-Long; Hou, Sai; Yu, Jun-Ling; Wu, Jia-Bin; Xia, Zhi-Cai; Latif, Adams; Gao, Rongbao; Su, Bin; et al.
Abstract We compared complete genome sequences of two strains of an avian influenza A (H5N6) virus isolated from a patient in Anhui Province with those of other strains from GenBank and Global initiative on sharing all influenza data (GISAID). The HA gene of the isolated virus shared homology with that of A/chicken/Zhejiang/727155/2014 (H5N6) at the level of similarity of 98%. The six internal genes of the Anhui strains were close to those of H9N2 viruses from Zhejiang, Shandong, and Guangdong provinces, with a similarity of 99%. In addition, the similarity between the internal antigens (NP and MP) of the isolated H5N6 virus and H7N9 and H10N8 viruses was 99%. Based on the data of phylogenetic analysis, the H5N6 influenza virus isolated in Anhui Province belonged to clade 2.3.4.4. The virus was shown to have molecular characteristics of highly pathogenic avian influenza viruses, including eight glycosylation sites and an amino acid sequence of the HA protein cleavage site, PLRERRRKKR/GLF, containing multiple basic amino acids. Additionally, the stalk domain of the NA protein was found to have a deletion in NA stalk region (11 amino acids in N6, positions 58–68). Our study demonstrated that the H5N6 virus from Anhui Province represented a triple-reassortant virus and could be highly pathogenic to humans. The prevalence of this virus should be closely monitored.